Discovery of a new intertidal species, Amblopusa vancouverensis from Vancouver Island, Canada with notes on Amblopusa brevipes Casey (Coleoptera, Staphylinidae, Aleocharinae) - Yoo, In-Seong; Ahn, Kee-Jeong (Zootaxa, 2020)
Amblopusa vancouverensis Yoo & Ahn, sp. nov. is described from Vancouver Island, Canada. The new species is compared with closely related species, A. brevipes Casey. Amblopusa brevipes is redescribed and the taxonomic characters of mouthparts and genitalia of both sexes are discussed and illustrated. New distributional record of A. brevipes for Agattu Island (the Aleutian Islands) is provided.